Komunikasi Pembangunan Agama Dalam Membangun Toleransi Agama (Analisis Sistem dan Aktor) - Sazali, Hasan (UIN Antasari, 2015)
Abstract : Religious development is an important constellation of nationaldevelopment. To address the spirit of pluralism and religious phenomenontoday, communication of religion development has become a scientific conceptapproach of several alternative science. Communication of religiousdevelopment is a communication process which is carried out to execute theplan in religious development by a state. This paper analyzes the problems ofreligious development using system analysis and actors as an approach to buildlogical thinking to the current situation.